New design method of the single stage distributed amplifier. (June 2016) - Amrani, Fayçal; Trabelsi, Mohamed; Youhami, Rachida; Aksas, Rabia
Abstract: This article describes a new design method of the single stage distributed amplifier, based on the approximation of the amplifier transducer gain by the Chebyshev polynomial. This method allows making a very significant improvement in bandwidth, compared with the conventional distributed amplifier with a single field effect transistor, and a significant reduction in ripple ratio with a slight broadening of the bandwidth compared with an identical amplifier topology designed with another method that we had developed. These improvements are of 128% in bandwidth compared with the conventional distributed amplifier. In addition, we can, with this method, design an amplifier so that it has the same performance as the conventional distributed amplifier with 4 transistors.